Multisensory Architecture: Implementation of Multisensory Experiences in a Resort - Kharisma, Budisetya; Buwono, Hanugrah Adhi; Hardi, Rachmat Taufick (Rumoh Journal of Architecture, 2024)
Spatial experience is an interaction between architecture (space) and its users (human) which is connected by the senses. Every significant spatial experience is a multi-sensory experience, whether being experienced consciously or not. Nowadays, there are many architectural design that place too much emphasis on visual elements or even just focus on visual elements, thus ignoring other sensory elements (ocularcentrism). Multisensory architecture is an architectural approach based on spatial experience that pays attention to the harmony of various senses on its design process. This paper explains how multisensory architecture, as a design approach, has an impact on space (the design object is a resort in Gading Serpong). This paper uses qualitative descriptive methods to explain spatial experiences that cannot be explained simply by visualization images. The objective of applying a multisensory architectural approach in this design is to improve the quality of space which will also have an impact on the physical and psychological health on its users. The design results (resort) by the author illustrate how each space is designed with all the senses in mind. All the senses in mind do not always take the form of presenting sensory experiences, but can also take the form of limiting sensory experiences. The multisensory experience presented in this design refers to the concept of a private island paradise, in which there are two spatial experience orientations in the form of "mountain" and "beach". The spaces described in this paper are the entrance, foyer, user’s circulation, hotel units and lounge. By using a multisensory architectural approach, a unique spatial experience is created and the quality of the spatial experience is increased